140 kHz, 1.2 ps pulses from an all-PM Yb-doped fiber master oscillator-power amplifier. (9th July 2021) - Liu, Yuxian; Liu, Guanyu; Zhao, Qiancheng; Cui, Jian; Lin, Junyu; Zhang, Dacheng
Abstract: We report on an environmentally stable mode-locked all polarization maintaining fiber laser with a nonlinear amplifying loop mirror (NALM) at a ultralow repetition rate. Experimentally, using different cavity lengths we have achieved stable mode-locking at different repetition rates. By carefully adjusting the length of the total fiber of NALM, we achieve stable broadband pulse trains with a repetition rate as low as 140 kHz. The pulses can be further amplified up to 27 μ J and compressed down to 1.16 ps. The laser system has potential application for industrial application.